If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ab = 3x + 12 Reorder the terms: ab = 12 + 3x Solving ab = 12 + 3x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by 'b'. a = 12b-1 + 3b-1x Simplifying a = 12b-1 + 3b-1x
| 4c-5c+8.4=3.6-2c-4.2 | | 63=3v | | 87+x=120 | | -45+x=-31 | | 4+6x=7+2x | | -2(-3x+2)=-6 | | 3(2b-4)=5(b+2) | | 105x^2-182x+56=0 | | 7a+8=8a-2 | | 3(4x+7)+9(x-1)=180 | | 3x-5-4x=6-2x | | s+1.2=-.2 | | 107-2x=25x+23 | | 3x-2=3(x-0.6666666666666666) | | x^4+12x^2-27=0 | | 63y-42=64y | | 7x-1+22(x-1)=180 | | 6(x-4)+9=2x+4(-3+x) | | 3x^3-8x^2+4x=0 | | 5x+3y+12x-7xy= | | 16=1d+6 | | 4x+8+2x=5x-1 | | -4x^2-6x+4=0 | | 5x+3+6x-1=90 | | 4p-3q+7p-2q= | | -6(3-3)-8(6x+5)=32 | | 20x-27x-8=0 | | 3(cq-5)=2(q+5) | | 2x+5x+42=0 | | 9x+9=7x+39 | | 5x*12=126,000 | | -12x-35x-18=0 |